(untitled) (Orfeu, 2023)
This article presents an overview of the academic production in the field of conducting, in order to allow a critical reflection on this area. To achieve this goal, we looked at the dissertations and thesis present in institutional repositories of public Brazilian graduate programs, deepening the search in the Brazilian Digital Library of Theses and Dissertations (BDTD), and also viewed the articles published in the journals of the Brazilian Association of Music Education (ABEM) and the National Association of Research and Graduate Studies in Music (OPUS). Finalizing the examination, we surveyed articles in the annals of ABEM and ANPPOM. The methodological procedure was exploratory research, with a time frame of the first 20 years of the 21st century (2001-2021). Thus, the collected data structure the present state of the art, expressing postulates, concepts and paradigms of conducting.